Вклад професора Д.Ф. Лихваря у створення колекцій рослин та розгортання наукової діяльності Центрального республіканського ботанічного саду АН УРСР - Rakhmetov, D.B.; Moroz, P.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2003)
The role of D.F. Likhvar in creation of collections of plants of cultural flora, and also in expansion of scientific activity of the Central Republican Botanical Gardens of Academy of Sciences of Ukraine during his becoming is shown.